2016
DOI: 10.7554/elife.14521
|View full text |Cite
|
Sign up to set email alerts
|

Lip movements entrain the observers’ low-frequency brain oscillations to facilitate speech intelligibility

Abstract: During continuous speech, lip movements provide visual temporal signals that facilitate speech processing. Here, using MEG we directly investigated how these visual signals interact with rhythmic brain activity in participants listening to and seeing the speaker. First, we investigated coherence between oscillatory brain activity and speaker’s lip movements and demonstrated significant entrainment in visual cortex. We then used partial coherence to remove contributions of the coherent auditory speech signal fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
227
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(279 citation statements)
references
References 62 publications
37
227
4
Order By: Relevance
“…Entrainment to auditory speech is strongest over auditory cortex (2,8,11,35) and central frontal sites (14). By contrast, our results show that entrainment to sign language is strongest at occipital and parietal channels, consistent with greater parietal activation during sign compared with speech (53).…”
Section: Neural Mechanisms Of Language Comprehension Across Sensorycontrasting
confidence: 50%
See 2 more Smart Citations
“…Entrainment to auditory speech is strongest over auditory cortex (2,8,11,35) and central frontal sites (14). By contrast, our results show that entrainment to sign language is strongest at occipital and parietal channels, consistent with greater parietal activation during sign compared with speech (53).…”
Section: Neural Mechanisms Of Language Comprehension Across Sensorycontrasting
confidence: 50%
“…Although these rhythmic preferences are not absolute [visual cortex also shows rhythmic oscillations in the delta/theta range (11,17,(34)(35)(36)(37)], differences between the sensory modalities are apparent when different frequency bands are directly compared. Auditory detection sensitivity depends on the phase of underlying delta-theta, but not alpha, oscillations (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neural entrainment to continuous visual speech has been previously studied in the context of physical, low-level information through the use of the acoustic envelope (Crosse et al, 2015a) and lip movements (Park et al, 2016). Park et al (2016) showed that high-level visual regions as well as speech processing regions specifically entrained to the visual component of speech.…”
Section: Discussionmentioning
confidence: 99%
“…And fMRI research on AV speech perception has shown increases in connectivity strength between putatively multisensory regions and visual cortex when the visual modality is more reliable (Nath and Beauchamp, 2011). In terms of continuous visual speech processing, recent MEG work found extensive (bilateral) entrainment of visual cortex to visual speech (lip movements) when the visual signal was relevant for speech comprehension (Park et al, 2016). Importantly, this entrainment was restricted to a much smaller area in early visual cortex (left-lateralized) when the visual speech was irrelevant.…”
Section: Introductionmentioning
confidence: 99%